Réponses

Meilleure réponse !
2014-01-09T15:38:34+01:00
Factoriser = transformer en mutiplication
a) 6x²+11x=    ( mise en évidence)
x ( 6x+11)
b) x²-2x+1=      (identité remarquable de la forme (x-y)²)
(x-1)²
c) (x+1) (x+5)+(x+1)(x+4)= (mise en évidence)
(x+1) ( x+5 + x+4) =
(x+1) (2x +9)
d) 2x(2-x)+3(-x+2)=
(2-x) (2x+3)
e) (-2x-4)(7x+3)+(7+x)(-2x-4)=
(-2 - 4) ( 7x+3 +7+x) =
(-2 -4) (8x+10)
f)  4x²+24x+36=
(2x+6)²          ( identités remarquables)
2014-01-09T15:50:19+01:00
A)6x²+11x= 2x(3x+5)+x

b)x²-2x+1= (x-1)(x-1)

c)(x+1)(x+5+x+4)=(x+1)(2x+9)
=2x²+11x+9

d)2x(2-x)+3(-x+2)
=4x-2x-3x+6=-x+6

e)(-2x-4)(7x+3+7+x)=
(-2x-4)(8x+10)=
-16x²-12x+40

f)4x²+24x+36=
(2x+6)(2x+6)